1966
DOI: 10.1103/physrev.144.504
|View full text |Cite
|
Sign up to set email alerts
|

Fermi Surface and Positron Annihilation in Yttrium

Abstract: The electronic structure of yttrium has been calculated at the equivalent of 6000 general points in the primitive Brillouin zone using the augmented-plane-wave method. The density of states and the Fermi surface are presented. The topology of the Fermi surface is discussed, and experimental results for de Haasvan Alphen measurements are predicted. Wave functions have also been calculated for each of the occupied eigenvalues, and these were used to study the angular distribution of radiation resulting from posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

1972
1972
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(38 citation statements)
references
References 6 publications
1
35
0
2
Order By: Relevance
“…ACAR experiments have shown that the momentum distribution of annihilating positrons follows the sample temperature down to 10 K (Hyodo, McMullen, and Stewart, 1986). In a few cases incomplete thermalization may be important, e.g., positrons implanted at a very low energy can escape the sample nonthermally through the surface [see Mills (1986), Nielsen, Lynn, andChen (1986), Huomo et al (1987), andNielsen (1987) and there are also related problematics in measurements made for nanocrystalline matter; see Sec. V.C].…”
Section: Experimental Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…ACAR experiments have shown that the momentum distribution of annihilating positrons follows the sample temperature down to 10 K (Hyodo, McMullen, and Stewart, 1986). In a few cases incomplete thermalization may be important, e.g., positrons implanted at a very low energy can escape the sample nonthermally through the surface [see Mills (1986), Nielsen, Lynn, andChen (1986), Huomo et al (1987), andNielsen (1987) and there are also related problematics in measurements made for nanocrystalline matter; see Sec. V.C].…”
Section: Experimental Techniquesmentioning
confidence: 99%
“…The augmented plane-wave (APW) method by Slater (1937) was used by several groups (Loucks, 1966;Wakoh, Kubo, and Yamashita, 1975;Kubo, Wakoh, and Yamashita, 1976;Gupta and Siegel, 1977, 1980a, 1980b in a non-selfconsistent fashion. The supercell approximation was used for localized positrons first by Gupta and Siegel (1977).…”
Section: F Numerical Approaches For Self-consistent Calculationsmentioning
confidence: 99%
“…Розрахунки зонної структури та поверхні Фермі Y виконав Лукс [25], а також Альтман та Бредлі [22]. Лукс використовував методу нерелятивістських приєднаних ТЕОРІЯ ВЗАЄМОДІЇ ФОНОНІВ З ЕЛЕКТРОНАМИ В МЕТАЛАХ 37 пласких хвиль.…”
Section: скандій і ітрійunclassified
“…Одержана ними повна густина станів ітрію дещо відрізнялась від тієї, що одержав Лукс. Як показано у [25], ці розбіжності зумов-лені різними способами побудови кристалічного потенціялу. Аль-тман і Бредли [22] представили кристалічний потенціял у вигля-ді суперпозиції потенціялів йонів Y 3 і потенціялу, зумовленого однорідним розподілом зарядової густини трьох електронів, а Лукс [25] застосував при визначені потенціялу схему Маттхейса [26].…”
Section: скандій і ітрійunclassified
“…17 Positron annihilation was used right from the beginning of such investigations, with early calculations by Loucks including a calculation of the positron wavefunction. 18 In a series of positron annihilation experiments on Y and its alloys with Gd, [19][20][21] Dugdale et al were able to experimentally establish the existence of this webbing, show that the size of the vector which spanned the webbing could be linked with the magnetic ordering vectors when small amounts of rare earth were alloyed into Y, 22 and monitor its evolution under doping.…”
Section: Helical Ordering In the Rare-earthsmentioning
confidence: 99%